Do outdoor adventure park activities increase visitors' well-being?. (September 2021) - Schlemmer, Philipp; Scholten, Tobias; Niedermeier, Martin; Kopp, Martin; Schnitzer, Martin
Abstract: Outdoor adventure activities have become more popular in recent decades, offering excitement and thrills to their consumers. There has been little research on whether or not outdoor adventure activities impact well-being, especially when these activities are consumed in an outdoor adventure park setting. Thus, this study examined the impact of outdoor adventure park visits on the well-being of (day) tourists by applying a quantitative between-subject pre-post-visit design ( n = 349). Results suggested short-term effects of outdoor adventure park activities on well-being, which were also impacted by gender patterns. The study at hand broadened existing discussions and literature in terms of the understanding of outdoor adventure park effects on visitors by (1) providing a before-after comparison of outdoor adventure park guests' well-being, (2) taking heed of socio-demographic predeterminations, and (3) gathering knowledge about how the duration of a stay at an outdoor adventure park effects changes in well-being.